KOSMOLOGI JAWA SEBAGAI LANDASAN FILOSOFIS ETIKA LINGKUNGAN - Haryati, Tri Astutik (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2017)
This present paper aimed to establish the philosophical foundation of environmental ethics through the perspectives of Javanese cosmology. Ontologically, Javanese cosmology tends to see the relation between human and nature as the unity of existence (Javanese: manunggalingkawulagusti). This kind of perspective can be instrumental to help positivistic-anthropocentric cosmology to be included within the mentality of enlightenment. Etymologically, Javanese cosmology builds upon ‘a sense’ reflecting on the systematisation of human experience in undergoing this life, which enables human to get a better knowledge of God as the creator of the universe. In an axiological way, Javanese cosmology accentuates the principle of harmony with nature, denoting the human’s appreciation of the nature that signifies the negation of a gap between subject and object. These reflections about Javanese cosmology point to the possibility of implementing norms that are used as a standard of human conduct, and that guide how practical human needs can be made in line with ethical and anthropological dimensions. Javanese cosmology therefore is thought not only to be capable of changing how human views nature. Rather, it is also thought to contribute to the development of environmental ethics that are beneficial to human in responding to the problem of environmental damage either on local level or global level.